2020
DOI: 10.21203/rs.3.rs-67888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How mu-Opioid Receptor Recognizes Fentanyl

Abstract: The opioid crisis has escalated during the COVID-19 pandemic. More than half of the overdose-related deaths are related to synthetic opioids represented by fentanyl which is a potent agonist of mu-opioid receptor (mOR). In recent years, crystal structures of mOR complexed with morphine derivatives have been determined; however, structural basis of mOR activation by fentanyl-like synthetic opioids remains lacking. Exploiting the X-ray structure of mOR bound to a morphinan ligand and several state-of-the-art sim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Previous MD simulation studies showed that the amide moiety of fentanyl could be stable in either the trans or cis conformation (Fig. 1D) in the MOR binding pocket, without any reported transition between these two conformations (de Waal et al, 2020;Lipinski et al, 2019;Podlewska et al, 2020;Ricarte et al, 2021;Vo et al, 2021). These results suggest the transition between the trans and cis conformations may have a relatively high energy barrier to overcome in the MD simulations, but these studies did not evaluate which conformation has lower energy.…”
Section: The Amide Moiety Of Fentanyl and Its Analogs Favors The Trans Conformationmentioning
confidence: 84%
See 4 more Smart Citations
“…Previous MD simulation studies showed that the amide moiety of fentanyl could be stable in either the trans or cis conformation (Fig. 1D) in the MOR binding pocket, without any reported transition between these two conformations (de Waal et al, 2020;Lipinski et al, 2019;Podlewska et al, 2020;Ricarte et al, 2021;Vo et al, 2021). These results suggest the transition between the trans and cis conformations may have a relatively high energy barrier to overcome in the MD simulations, but these studies did not evaluate which conformation has lower energy.…”
Section: The Amide Moiety Of Fentanyl and Its Analogs Favors The Trans Conformationmentioning
confidence: 84%
“…In addition, the conformations of the bound fentanyl are also different in these studies. The dihedral angle between amide carbonyl and aniline was in the trans configuration in the Ricarte, de Waal, and Lipinski poses (de Waal et al, 2020;Lipinski et al, 2019;Ricarte et al, 2021), and cis in the Vo and Podleska poses (Podlewska et al, 2020;Vo et al, 2021) (see the trans and cis definitions in Fig. 1D).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations